Kajian Uses and Gratification Pengguna Media Sosial Untuk Mendukung Performa Penjualan Film Melalui Opini Pra-Konsumsi - Romdhi Fatkhur Rozi; Romdhi Fatkhur Rozi (Program Studi Film dan Televisi Universitas Jember, 2023)
The widespread use of social media has also affected the business aspects of creative industries such as film production and marketing. This happens because social media is used as an open public discussion space and brings together social media users with customers and potential customers of creative industry businesses. The film industry is a field that requires special strategies in the promotion process due to its dynamic nature and its competitive scheme that changes every week. This makes pre-consumption opinions made by social media users important as it can affect the sales performance of the released film. This study uses uses and gratification theory to discover how social media users use digital spaces to get satisfaction. This study separates individual engagement and interactive engagement as two important things that determine customer satisfaction in using social media and how it influences the pre-consumption opinions that circulate. This study is also useful for academics who have a focus of study on media studies, communication, business, as well as actors in the creative industry to determine promotional strategies from the time of film release until the product gets its gross profit.